Exploring Cross-Modal Influences on the Evaluation of Indoor-Environmental Conditions - Berger, Christiane; Mahdavi, Ardeshir (Frontiers in Built Environment, 2021)
Occupants' comfort requirements influence buildings' indoor-environmental and energy performance. Occupants are typically exposed to a multitude of indoor-environmental factors, including a variety of different thermal, auditory, visual, and air quality conditions. However, the bulk of past research and derivative indoor-environmental codes and standards concerning occupants' comfort address the multiple indoor-environmental stimuli in isolation. Starting from a brief review of past research on occupants' multi-perceptual indoor environment assessments, the present study pursues an experimental approach to explore potential cross-modal effects on occupants' evaluation of indoor environment's thermal, visual, and acoustic aspects. In this context, a laboratory space including two adjacent identical mock-up office rooms was used to conduct multi-aspect parametric studies with human participants. Different thermal, visual, and auditory conditions were maintained in these two units. In the course of the present study 296 participants were exposed, on a short-term basis, to different combinations of thermal, visual, and auditory conditions. The experiments were intended to explore if participants' evaluation of one aspect of the indoor environment could be influenced by differences in the values pertaining to the other aspects. The experimental results are presented and discussed, including their limitations.